2004
DOI: 10.1136/bjo.2003.037663
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomised comparison of single and three piece acrylic foldable intraocular lenses

Abstract: Aims: To compare the postoperative performance of single and three piece acrylic foldable intraocular lenses (IOLs). Methods: 20 patients underwent bilateral cataract surgery with a single piece SA30AL IOL in one eye and a three piece MA30BA IOL in the other eye. The eyes were randomly assigned to either a single or three piece lens. The amount of IOL decentration and tilt, area of anterior capsule opening, and degree of posterior capsule opacification were measured using the Scheimpflug anterior segment analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 36 publications
2
19
0
2
Order By: Relevance
“…There was a small difference in PCO frequency between the hydrophobic one-piece and three-piece IOLs, but there was also a significant difference in age and prevalence of diabetes between these groups. Previous studies have shown no difference in PCO frequency between one-piece and three-piece IOL design in comparable groups (Nejima et al 2004(Nejima et al , 2006Leydolt et al 2007). That hydrophilic IOLs have a higher incidence of PCO than hydrophobic IOLs has been shown before, and this study confirms that this is the case even in a clinical setting with long-term follow-up (Billotte & Berdaux 2004).…”
Section: Discussionmentioning
confidence: 82%
“…There was a small difference in PCO frequency between the hydrophobic one-piece and three-piece IOLs, but there was also a significant difference in age and prevalence of diabetes between these groups. Previous studies have shown no difference in PCO frequency between one-piece and three-piece IOL design in comparable groups (Nejima et al 2004(Nejima et al , 2006Leydolt et al 2007). That hydrophilic IOLs have a higher incidence of PCO than hydrophobic IOLs has been shown before, and this study confirms that this is the case even in a clinical setting with long-term follow-up (Billotte & Berdaux 2004).…”
Section: Discussionmentioning
confidence: 82%
“…The clinical literature includes numerous reports of IOL tilt and decentration at different times after surgery or with different IOL types using commercial Scheimpflug instruments. [22][23][24][25][26][27][28] With these instruments, the optical distortion is presumably not corrected. Only a recent study of IOL tilt and decentration in eyes with phakic lenses 29 using a Nidek Scheimpflug system mentions that images were corrected using custom algorithms.…”
Section: J Cataract Refract Surg 2007; 33:418-429 Q 2007 Ascrs and Escrsmentioning
confidence: 98%
“…9 Measurements of the IOL tilt and decentration measured with Scheimpflug imaging have been reported in the clinical literature, although in these instruments optical distortion is presumably not corrected. [10][11][12][13][14][15][16] Custom correcting algorithms have been used in a report of IOL tilt and decentration of phakic lenses and measured with a refurbished Nidek Scheimpflug system, which is no longer commercially available. 17 Here, we review the development (hardware and software), validation and measurements of two instruments based on Purkinje and Scheimpflug imaging, developed at the Visual Optics and Biophotonics Laboratory (Instituto de Óptica, Consejo Superior de Investigaciones Científicas).…”
mentioning
confidence: 99%